IDÍLIO OU PESADELO? A GENEALOGIA DO PODER EM ADMIRÁVEL MUNDO NOVO DE ALDOUS HUXLEY - Joanico, Lennon Moraes (2016)
This dissertation aims to examine how the control mechanisms and thus power are organized in the utopian narrative Brave New World, written by Aldous Huxley, as well as highlight the importance of such issues for the narrative’s understanding. For this, the discussion will avail concepts and reflections proposed by philosopher Michel Foucault, specifically, but not exclusively, in Microphysics of Power (2013), in which the theoretic ponders about the micro-power relations, the body, discipline and the individual as the result of power relations. Thereby, the study will problematize the multiplicities of control and power constitutive of the interrelations between the social and the individual, showing the potential positive and negative aspects of power settings in the narrative. With this, it expected that the issues that will be listed here can contribute to the expansion of reflections about Aldous Huxley's work, and also, it can further the discussions concerning to the control and power's issues in other literary works.